Artemis Fowl. The Arctic incident : the graphic novel - Colfer, Eoin (Colfer, Eoin. Artemis Fowl, 2009)
In order to free his father from the Russian Mafiya, Artemis must join forces with the fairy police and his familiar nemesis, Captain Holly Short.